Chromoblastomycosis caused by Alternaria infectoria, concurrent with myiasis, in a recipient of a kidney transplant: a compelling case report - Mahmoudi, Hamidreza; Ramezanalipour, Zahra; Khansari, Mahmoud; Meijer, Eelco F. J.; Mahmoudi, Shahram; Spruijtenburg, Bram; Rahimi Foroushani, Abbas; Gramishoar, Mohsen; Kamali Sarvestani, Hasti (Frontiers in Medicine, 2024)
Neglected tropical diseases (NTDs) pose a significant threat to the health of millions of people worldwide, particularly in impoverished populations in tropical and subtropical regions. The World Health Organization (WHO) considers certain fungal infections, such as chromoblastomycosis, as NTDs. Chromoblastomycosis is a chronic fungal infection affecting the skin and subcutaneous tissue, primarily found in tropical and subtropical regions of Latin America, Africa, and Asia. This case report presents a 46-year-old female patient with chromoblastomycosis who had a history of renal transplantation and was receiving immunosuppressive therapy. The patient exhibited dark, verrucous, and ulcerative lesions on the legs, and the diagnosis was confirmed through the microscopic examination of skin scrapings by observing medlar bodies. Two sequential fungal tissue cultures and ITS sequencing verified the presence of Alternaria infectoria, not formerly described in chromoblastomycosis. Moreover, observation of fly larvae in the lesions verified the diagnosis of myiasis. Treatment with voriconazole and terbinafine resulted in complete resolution of the lesions after 5 months. This case emphasizes the importance of considering chromoblastomycosis in individuals with occupational exposure in tropical areas, as well as the challenges associated with its diagnosis, coinfections, and treatment.